Out of the blue! Valuing the disability market in tourism, Report of the 5th National Nican Conference, Perth 20-22 September 2004. - Packer, Tanya; Carter, M. (2004)
The Australian Government, Department of Industry, Tourism and Resources White Paper (2004) calls on all stakeholders to "capture, maintain and grow Australia's future international and domestic tourism market" (p.vi).Western Australia's vision is to develop an international reputation as Australia's best-equipped and most hospitable accessible tourism destination for business and leisure tourists with a disability (Perth Convention Bureau, 2004).Out of the Blue, Valuing the Disability Market in Tourism, the 5th National NICAN Conference, advanced both of these visions by bringing together policy makers, academics, tourism providers and most importantly, the actual market people with disabilities.In opening the conference Sheila McHale, WA Minister for Community Development; Women's Interests; Seniors and Youth; Disability Services; Culture and Arts, identified the significant place that people with disabilities, their families and carers hold within our community. She recognised the connection between ageing and increasing numbers of people with disabilities. Ms McHale acknowledged the rights of all members of our community to participate in the tourism market and the benefits of accessible tourism that will flow on to all.Her most important announcement was the formation of the newly appointed WA Accessible Tourism Taskforce.Over the three-day conference, successes, shortcomings, issues, and recommendations were addressed, discussed and debated among and between participants, bringing all sectors into the discussion. The final day focused on the way forward, outlining key issues, making recommendations and identifying those responsible for action.Bob Kucera, WA Minister for Tourism; Small Business; Sport and Recreation; Peel and the South West, closed the conference on final day. Mr Kucera encouraged tourism operators to recognise the importance of the accessible tourism market and work with the disability sector to ensure Western Australia becomes the nation's leading destination for people with disabilities.The message from participants was clear we have an accessible tourism industry, but it is fragmented and lacks universality, and information is unreliable and inaccurate. As a result, access is not assured and the overall tourism experience for people with disabilities lags far behind that provided to other segments of the population. Recommendations from this conference will set the agenda for the foreseeable future, helping Australia and its states further develop a sustainable, capable, accessible and highly reputable tourism industry.This report provides an overview of the conference and summarizes the key issues identified and recommendations made. Presentation of these issues and recommendations have been organised as follows: Key Imperatives for Change Developing Accessible Tourism Identifying Current Issues Conference RecommendationsConference recommendations are linked to the six key strategies named in the Australian Government Tourism White Paper Implementation Plan. This is done to emphasize that accessible tourism is a legitimate tourism market that must be integrated and developed using the same mechanisms used for building other segments of this strong and vibrant industry. The magnitude of the accessible tourism market makes it part of the mainstream and as with all markets, has unique characteristics that must be understood before it can be effectively developed and promoted.Throughout the report, examples of best practice are included to illustrate what is possible. Negative examples serve to demonstrate the need for change.